Author Correction: Quasi-static and dynamic experimental studies on the tensile strength and failure pattern of concrete and mortar discs - Jin, X.; Hou, C.; Fan, X.; Lu, Chunsheng; Yang, H.; Shu, X.; Wang, Z. (2022)
The original version of this Article contained errors. The article contained typos in two equations. The Eqs. (2) and (10) should read (Formula presented.) Additionally, there were errors in the average quasi-static splitting strengths of concrete and mortar. “As listed in Supplementary Table S1, the average splitting tensile strengths are 2.25 and 2.73 MPa for 5 concrete specimens with thicknesses of 30 and 55 mm; while their corresponding values for 5 mortar specimens are 3.44 and 3.56 MPa, respectively.” should read: “As listed in Supplementary Table S1, the average splitting tensile strengths are 2.64 and 2.60 MPa for 10 concrete specimens with thicknesses of 30 and 55 mm; while their corresponding values for 10 mortar specimens are 3.47 and 3.35 MPa, respectively.” Finally, in Figure 7(a), the transmission wave signal was amplified twice without correct marking. The corrected Figure 7(a) appears below. These errors do not affect the conclusions of the Article.